2022
DOI: 10.1039/d2cc03970b
|View full text |Cite
|
Sign up to set email alerts
|

Chasing protons in lithium-ion batteries

Abstract: Parasitic reactions between delithiated cathode materials and non-aqueous electrolytes have been a major barrier that limits the upper cutoff potential of the cathode materials. It is of great importance to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(98 reference statements)
0
5
0
Order By: Relevance
“…Reported oxidation potentials for EC vary, but if we limit our consideration to measurements made using nonreactive electrodes such as platinum or glassy carbon, aiming to eliminate the possibility of reactions between EC and electrode surfaces, the reported values are between 4.8 and 6.5 V. , Even the low end of this range is considerably higher than typical LIB operating potentials. However, Chen recently suggested that concentration effects may decrease the effective oxidation potential of EC. That is, if the products of electrochemical oxidation are sufficiently short-lived or in sufficiently low concentration at steady state, the reaction could become favorable at potentials below EC’s standard oxidation potential.…”
mentioning
confidence: 99%
“…Reported oxidation potentials for EC vary, but if we limit our consideration to measurements made using nonreactive electrodes such as platinum or glassy carbon, aiming to eliminate the possibility of reactions between EC and electrode surfaces, the reported values are between 4.8 and 6.5 V. , Even the low end of this range is considerably higher than typical LIB operating potentials. However, Chen recently suggested that concentration effects may decrease the effective oxidation potential of EC. That is, if the products of electrochemical oxidation are sufficiently short-lived or in sufficiently low concentration at steady state, the reaction could become favorable at potentials below EC’s standard oxidation potential.…”
mentioning
confidence: 99%
“…Oxidation of the electrolyte at the cathode surface generates protons that diffuse into the bulk of NiO 2 . We predict that proton defects energetically favor O1 stacking over the O3 stacking in NiO 2 because stronger hydrogen bonds form at the proton defect with O1 stacking. We show that protons can diffuse in the space between layers of NiO 2 .…”
Section: Discussionmentioning
confidence: 96%
“…With the continuous evolution of new concepts and new characterization capacities, the chemical and physical image of a good CEI is continuously updating, but a consensus on universally good CEI has not been achieved yet. On the other hand, there is an emerging effort to quantitatively measure the electrochemical functionality of the CEI layer, to block the electron transfer between the electrolyte and the electrode materials, using advanced electrochemical characterization such as high precision columbic efficiency (HPCE) [26,27] and high-precision leakage current (HpLC) [28][29][30][31] measurements. Both HPCE and HpLC results show that, even with the presence of the best SEI or CEI, there are persistent parasitic reactions ongoing inside lithium-ion cells.…”
Section: Introductionmentioning
confidence: 99%